U.S. Department of Defense handbook of military symbols - Underwood, Peter T. (Skyhorse Publishing, 2013)
The system contained in this handbook , based on MIL-STD-2525C, is designed to eliminate conflicts within various symbol sets and to establish a core set of common symbology under one Department of Defense standard.